PENGARUH ELECTRONIC WORD OF MOUTH DI MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI KONSUMEN PADA DISTRO BATTLEBOOM PALU - PUTRA, CHANDRA ANANTA (Fakultas Ekonomi Universitas Tadulako, 2015)
This study aims to determine and analyze the influence of electronic word of mouth variables in social media Instagram of consumer buying interest in Battleboom Palu Distro. The type of research used is quantitative (indicating the relationship between variables). The population in this study is the whole followers account Instagram Distro Battleboom Palu number is not known with certainty The sampling technique to determine the sample that will be use in this research using non probability sampling technique, that is purposive sampling. With the number of samples as much as 100 respondents. Data collection using questionnaire. Data analysis method used multiple linear regression analysis. The results showed that (1) There is influence of electronic word of mouth simultaneously to consumer buying interest in Distro Battleboom Palu (2) partially electronic word of mouth sub variable content and intensity influential significant to consumer buying interest in Distro Battleboom Palu (3) and partially electronic word of mouth sub variable negative valence of opinion and positive valence of opinion have no significant effect on consumer buying interest in Distro Battleboom Palu.